Molecular mechanisms of epigenetic inheritance: Possible evolutionary implications. (January 2020) - Sarkies, Peter
Abstract: Recently interest in multi-generational epigenetic phenomena have been fuelled by highly reproducible intergenerational and transgenerational inheritance paradigms in several model organisms. Such paradigms are essential in order to begin to use genetics to unpick the mechanistic bases of how epigenetic information may be transmitted between generations; indeed great strides have been made towards understanding these mechanisms. Far less well understood is the relationship between epigenetic inheritance, ecology and evolution. In this review I focus on potential connections between laboratory studies of transgenerational epigenetic inheritance phenomena and evolutionary processes that occur in natural populations. In the first section, I consider whether transgenerational epigenetic inheritance might provide an advantage to organisms over the short term in adapting to their environment. Second, I consider whether epigenetic changes can contribute to the evolution of species by contributing to stable phenotypic variation within a population. Finally I discuss whether epigenetic changes could influence evolution by either directly or indirectly promoting DNA sequence changes that could impact phenotypic divergence. Additionally, I will discuss how epigenetic changes could influence the evolution of human cancer and thus be directly relevant for the development of this disease.